Connecting meanings of ageing, consumption, and information and communication technologies through practice. (29th May 2020) - Mansvelt, Juliana; Elms, Jonathan; Dodds, Sarah
Abstract: Practices involving the consumption of Information and Communication Technology (ICT) are increasingly important to the maintenance of everyday life for older New Zealanders. Developing competency with ICT can provide a way of challenging negative discourses of ageing. Interviews with 20 older New Zealanders reveal that "keeping up" with the times, with changing technologies, and with others is a means by which to shape aged subjectivities. However, while competency in ICT practices enables participants to refute discourses of ageing that locate older people negatively as part of an aged digital divide, it can also work to reproduce this divide. Consequently, understanding the nuanced and situated nature of meanings related to ICT practice is necessary in order to interrogate normative assumptions associated with the "more than human" possibilities of ageing well.